Historical dictionary of Australian and New Zealand cinema - Aveyard, Karina; Moran, Albert; Vieth, Errol, 1950- (Historical dictionaries of literature and the arts., 2018)
This second edition of Historical Dictionary of Australian and New Zealand Cinema contains a chronology, an introduction, and an extensive bibliography. The dictionary section has over 700 cross-referenced entries on leading films as well as many directors, writers, actors and producers.